Unmasking Ocular Rosacea: Diagnostic Challenges and Evolving Management (Canadian Eye Care Today, 2025)
Ocular rosacea is a chronic inflammatory condition affecting the eyes, and is often associated with cutaneous rosacea. It is a common yet frequently underdiagnosed disorder that can lead to significant ocular morbidity and, in severe cases, vision loss.